Determinants of complementary feeding practices among children aged 6-24 months in urban slums of Pune, Maharashtra, in India - Angeline Jeyakumar; Prasad Babar; Pramila Menon; Raji Nair; Suresh Jungari; Aishwarya Medhekar; Bhrunal Prakshale; Jasmine Shaikh; Merlin Chacko; Mohini Nikam; Purva More; Shakila Nayel; et al. (BMC, 2023)
Abstract Background Inequalities in child feeding practices are evident in urban slums in developing nations. Our study identified the determinants of complementary feeding (CF) practices in the informal settings of Pune, India, a district close to the business capital of India. Methods Employing a cross-sectional study design, 1066 mother-children dyads were surveyed. Five indicators defined by the WHO were used to study complementary feeding practices. Determinants of complementary feeding practices were identified using multivariate analyses. Results Timely initiation of CF was reported by 42%. Minimum acceptable diet (MAD), minimum meal frequency (MMF), and Diet Diversity Score > 4 were achieved by 14.9%, 76.5%, and 16.4%, respectively. Continued breastfeeding (CBF) at 2 years, and feeding processed foods were practiced by 94% and 50%, respectively. Among the maternal characteristics, a mother's age > 30 years at pregnancy was less likely to achieve DD [AOR: 0.195 (CI 0.047-0.809)] and MAD [AOR: 0.231 (CI 0.056-0.960)]. Mothers with lower education were less likely to meet MMF [AOR: 0.302 (0.113-0.807)], MAD [AOR: 0.505 (CI 0.295-0.867)] and to introduce formula feeds (FF) [AOR: 0.417 (0.193- 0.899)]. Among obstetric characteristics, birth spacing < 33 months was less likely to achieve DD [AOR: 0.594 (CI 0.365-0.965)] and CBF [AOR: 0.562 (CI: 0.322-0.982)]. Receiving IYCF counseling only during postnatal care hindered the timely initiation of CF [AOR: 0.638 (0.415-0.981)]. Very Low Birth Weight increased the odds of achieving DD [AOR: 2.384 (1.007-5.644)] and MAD [AOR: 2.588(CI: 1.054-6.352)], while low birth weight increased the odds of children being introduced to processed foods [AOR: 1.370 (CI: 1.056-1.776)]. Concerning socio-economic status, being above the poverty line increased the odds of achieving MMF, [AOR: 1.851 (1.005-3.407)]. Other backward castes showed higher odds of achieving MAD [AOR: 2.191 (1.208-3.973)] and undisclosed caste in our study setting decreased the odds of FF [AOR: 0.339 (0.170-0.677)]. Bottle feeding interfered with MMF [AOR: 0.440 (0.317-0.611)] and CBF [AOR: 0.153 (0.105-0.224)]. Conclusion Investing in maternal education and IYCF counseling during both ANC and PNC to provide nutritious complementary foods alongside addressing poverty should be a national priority to prevent the double burden of undernutrition at an early age in informal settings.